The clinical effectiveness of therapeutic exercises alone and in combination with orthotic bracing in the treatment of lateral epicondylalgia - Flanders, Megan (2012)
Dissertation submitted in partial compliance with the requirements for the Master’s Degree in Technology: Chiropractic, Durban University of Technology, 2012. === Lateral epicondylalgia (L.E) is a common diagnosis in elbow pathology. The aetiology is poorly understood but it is generally accepted to be as a result of repetitive microtrauma, affecting the proximal end of the extensor carpi radialis brevis tendon. Elbow bracing and exercise modification are often utilised by sufferers in order to reduce symptoms. In addition, there have been multiple treatment regimes used in practice to treat L.E, but none has stood out as being more effective than another. Thus, the aim of this study was to investigate the relative clinical effectiveness of therapeutic exercises alone and in combination with orthotic bracing, in terms of subjective and objective clinical findings. Methods This stratified, quantitative, prospective clinical trial consisted of two equal groups (n=15) diagnosed with L.E. Group One consisted of a strengthening and stretching programme alone, and Group Two consisted of a combination of the same programme and an orthotic brace. The participants performed the programme daily at home for six weeks, and the brace was worn throughout the day for six weeks. Each participant was assessed before, during and after the programme, in terms of subjective and objective clinical data which was then statistically analysed using SPSS version 18. Repeated measures ANOVA testing was also used to compare the outcomes between the groups over the time points. Results Both groups showed significant statistical improvement in terms of all the outcome measures. The groups also showed a clinically significant improvement for all the outcome measures except pressure pain threshold where Group Two showed clinically significant improvement over Group One. v Conclusion The results show that there was negligible benefit when combining an orthotic brace with therapeutic exercises as opposed to performing the therapeutic exercises alone.